Influence of Selected Environmental Factors on the Business Type of Dentist's Practice in Germany: A Multi-Criteria Decision-Making Process With an Analytical Hierarchy Process - David Stein DDS (SAGE Publishing, 2023)
In the interests of satisfying the dental services demands of German citizens area-wide, constant, and thoughtful planning of supply and demand is essential. With an anonymous online survey of 375 dentists a pairwise comparison of 9 factors extracted as relevant from the existing scientific literature were analyzed with an analytic hierarchy process (AHP) and ranked considering the various business types. In general, 5 local environmental factors have a dominant impact on founders' decision in German dentistry. In order: environment for the family, quality of life in private environment, real income, location of the practice, infrastructure. Real income is in first place ( p  = 0.287) for dentists who want to start a new single practice. For preferring a new community practice, it is on third place ( p  = 0.177) and for dentists who favor a takeover a single practice ( p  = 0.130) or joining a community practice ( p  = 0.096) or employment ( p  = 0.111) it is fourth place. For this purpose, the location of the practice is of greater priority than the real income for dentists who prefer not to start a new practice. The AHP method is a way to picture a priority list out of all relevant factors for setting up of a dental practice.